2000
DOI: 10.1093/deafed/5.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Reading Optimally Builds on Spoken Language: Implications for Deaf Readers

Abstract: Reading is not merely "language by eye." Rather, it builds fundamentally on primary language processes. For hearing readers, this means that spoken language processes, including phonological processes, are critical to high achievement in reading. We examine the implications of this fact for deaf readers by considering the relationship between language and reading and by reviewing the research on the use of phonology by deaf readers. The research, although mixed in its results, suggests that the use of phonolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
116
3
28

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(156 citation statements)
references
References 48 publications
2
116
3
28
Order By: Relevance
“…Importantly, for deaf skilled readers error percentages were similar for pseudohomophones and control nonwords, suggesting that they did not activate phonological codes. Since our sample of deaf readers showed proficient reading scores but no evidence of phonological encoding, these results cast doubt on the hypothesis that deaf individuals need to access phonology in reading tasks to be competent readers (Perfetti & Sandak, 2000).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Importantly, for deaf skilled readers error percentages were similar for pseudohomophones and control nonwords, suggesting that they did not activate phonological codes. Since our sample of deaf readers showed proficient reading scores but no evidence of phonological encoding, these results cast doubt on the hypothesis that deaf individuals need to access phonology in reading tasks to be competent readers (Perfetti & Sandak, 2000).…”
Section: Discussioncontrasting
confidence: 69%
“…However, most deaf people never achieve a good reading level and lag behind their hearing peers (Conrad, 1979;Taxler, 2000). Various authors have suggested that reduced access to speech phonology is the main underlying cause of their reading difficulties and the high percentage of deaf people who make a great effort to learn to read (Hanson & Fowler, 1987;Perfetti & Sandak, 2000). Even so, it is unclear whether, for example, explicit training of phonological awareness helps deaf individuals to achieve high reading proficiency (Campbell & Wright, 1988;Izzo, 2002;Nielsen & Luetke-Stahlman, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to assume that deaf children who use speech learn to read in essentially the same way as hearing children, i.e. through the use of a phonological code (see Perfetti & Sandak, 2000). However, it is possible that signing deaf children may also learn to read in broadly the same manner because research suggests that similar skills are important for their reading development.…”
Section: Theories Of How Deaf Children Learn To Readmentioning
confidence: 99%
“…This result is surprising, as wellspecified phonological representations have been considered important for reading development as they underlie phonological awareness skill, which is assumed to be a metalinguistic skill underpinning phonological recoding and reading development (Snowling & Hulme 2012). This set of skills is considered by many to be vital even for a prelingually profoundly deaf reader (see Perfetti & Sandak 2000). Without them the underlying representations of words are poorly specified and their lexical structures are not segmentally organised and available at the syllabic, onset-rime or phonemic level (Swan & Goswami 1997).…”
Section: Introductionmentioning
confidence: 99%